Identification of Cyanide in Sediment of River in Hulawa Village - Rahman Suleman; Yeyen Afrianti Amma (JOURNAL OF NONCOMMUNICABLE DISEASES, 2022)
(1) Background: mining activities in Hulawa Village have caused heavy metal contamination in the surrounding environmental ecosystem. This is caused by the waste from gold processing which is dumped directly into the river body. The purpose of this study was to determine the Cyanide content in the sediment river in Hulawa Village; (2) Methods: this research is a descriptive study, using a purposive sampling method, with the sampling location at the midpoint of the river. This research was conducted in August-September 2020. The sediment sampling technique used the JPHA guidelines, and the cyanide examination in the sediment used the AAS test; (3) Result: the sediment samples obtained were then taken to the WLN laboratory in Manado to be tested for cyanide content. The test results showed that the cyanide content in the sediment was <0.5 mg/kg; (4) Conclusion: apart from heavy metal Mercury (Hg), the river in Hulawa Village has also been polluted by heavy metal Cyanide (CN). Cyanide content is still less than 0.5 mg/kg due to its not yet intensive use. However, if used continuously by miners, the possibility of cyanide accumulating in large quantities cannot be avoided, and this can have a health impact on the people in Hulawa Village.